Overweight and obesity in people living with HIV - Christefany Régia Braz Costa; Elizabete Santos Melo; Marcela Antonini; Priscila Silva Pontes; Elucir Gir; Renata Karina Reis
ABSTRACT Objective To identify overweight and obesity and as associated variables in people living with HIV. Method Cross-sectional, quantitative and analytical study, developed in specialized services in southeastern Brazil. Individual specifics were carried out from 2014 to 2016. Pearson's Chi-Square test, Logistic Regression and OddsRatio (OR) were used. Results Of the 340 respondents, 47.7% were overweight. The highest abdominal circumferences and lipid changes were predominantly among the highest body mass index (BMI). The greatest chances of obtaining BMI values>25 kg/m² were among men (OR: 1.87; 95% CI: 1.02-2.42), having metabolic syndrome (OR: 5.66; 95% CI: 3.26-9.83) and the undue (OR: 3.89; 95% CI: 2.17-7.00). However, having self-reported hypertension was configured as a protective factor (OR: 0.18; 95% CI: 0.08-0.44). Conclusion The frequency of obesity and overweight between PLHIV was high. There was an association of male gender, metabolic syndrome and smoking with weight gain. The presence of self-reported hypertension was considered a protective factor.